”Шэлжи мэлон” хэмээх зохиолын С.Шагжийн орчуулгын тухай - Д. Бүрнээ. (Acta Mongolica, 2005)
The Buddhist and philosophical work, "Crystal Mirrior", by the Tibetan scholar, Luvsanchoijinnyam (1737-1802, consisting of 12 chapters was translated in part into Russian, English, German, and Japanese. The complete translation was done by the Mongolian scholar, S. Shagj, in 1924; the manuscript is preserved in a 16-volume in the Central State Public Library of Mongolia. The article is about Shagj’s usage of Gonlun monastery’s block-print, and some features of his lexical and writing style.